OPTIMIZING EMPLOYEE PERFORMANCE VIA HUMAN RESOURCE DEVELOPMENT: INSIGHTS FROM RAHAYU MALANG COOPERATIVE - Moh. Romli; Hadi Sunaryo; Supriyanto (Pena Cendekia Insani, 2025)
This study aims to develop a model of human resource (HR) development to improve employee performance at the Rahayu Savings and Loan Cooperative (KSP) in Malang. Using a descriptive qualitative method, data were collected through interviews, observation, and documentation. Results show that continuous training, competency development, work motivation, and structured performance evaluations significantly improve employee performance. The model emphasizes transformational leadership, a cooperative work culture, and organizational learning as essential for performance enhancement. This study offers valuable insights for HR management in cooperatives to adapt to environmental changes and focus on results.